Characterization of Pectobacterium carotovorum subsp. carotovorum isolates from a recent outbreak on cabbage in Bosnia and Herzegovina - Popović, Tatjana; Jelušić, Aleksandra; Marković, Sanja; Iličić, Renata (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
The causal agent of soft rot disease associated with a cabbage outbreak in Semberija region, Bosnia and Herzegovina, in 2018 was identified and characterized. Symptoms appeared in the form of water-soaked lesions on leaves and specific odour. Disease incidence ranged from 20% to 30%. The causal pathogen was isolated on nutrient agar (NA), King’s B and crystal violet pectate (CVP) media. Eight creamy-white, round and convex bacterial isolates, which produced characteristic pits on CVP medium were taken as representative. They were gram negative, facultative anaerobe, oxidase negative, catalase positive, nonfluorescent on King’s B medium, levan and arginine dehydrolase negative. The isolates were able to cause soft rot on cabbage and potato tuber slices 24 h after inoculation under conditions of high relative humidity. Polymerase chain reaction (PCR) was performed for preliminary identification by using three specific primer sets: F0145/E2477 (specific for Pectobacterium carotovorum subsp. carotovorum), Br1f/L1r (specific for P. carotovorum subsp. brasiliensis) and ECA1f/ECA2r (specific for P. atrosepticum). All isolates produced the band size of 666 bp with F0145/E2477 primer pair, indicating that they belong to the species P. carotovorum subsp. carotovorum. Further genetic characterization was based on sequence analysis of the gapA and mdh housekeeping genes. BLAST analysis confirmed 99.39% (Q. cover 100%, E. value 0.0) and 100% (Q. cover 100%, E. value 0.0) identity of the isolates with P. carotovorum subsp. carotovorum strains deposited in the NCBI database as M34 (KY047594) for gapA and Pcc t0437 (KC337296) for mdh genes, respectively. Phylogenetic analysis showed genetic homogeneity among the cabbage isolates.